Artistic Originality of the Historical Story "Taras Bulba" in the Collection "Mirgorod" (Texas Journal of Multidisciplinary Studies, 2022)
The article examines one of the important and complex issues in the work of N.V. Gogol - his understanding of history and historical personality, as well as their artistic embodiment in the collection "Mirgorod".